Benin : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report, 1998)
This Selected Issues paper and Statistical Appendix examines some aspects of the civil service reform in Benin. It describes the main features of the promotion and compensation system currently in place; assesses the early efforts at reforming the civil service; and examines the main measures envisaged for 1998-2001. The paper assesses the impact of savings and loan associations on financial intermediation. It reviews the development of savings and loan associations in Benin, with particular focus on Federation of Rural Savings and Loan Cooperatives (FECECAM) because of its leading role in the system.